2020
DOI: 10.3390/microorganisms8030315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Yeasts on Physicochemical and Oenological Properties of Red Dragon Fruit Wine Fermented with Saccharomyces cerevisiae, Torulaspora delbrueckii and Lachancea thermotolerans

Abstract: A new type of fruit wine made from red dragon fruit juice was produced through alcoholic fermentation (AF) with different yeasts: Saccharomyces cerevisiae EC-1118, Torulaspora delbrueckii Biodiva and Lachancea thermotolerans Concerto. Complete AF with similar fermentation rates in terms of sugar utilisation and ethanol production (8–9%, v/v) was achieved by three yeast strains. T. delbrueckii produced a significantly lower amount of glycerol and acetic acid, while L. thermotolerans produced more lactic and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…It was statistically observed that the yeast with the lowest fermentation power was the F108 strain fermenting in the presence of low SO 2 and at low temperature (7.74 ± 0.04% v / v ), and the one that showed the highest fermentation power was the CONCERTO yeast (10.69 ± 1.32% v / v ) with low SO 2 and at high temperature. These results agree with previously reported information where the fermentative performance of the commercial strain Lt CONCERTO is really weak in a range of 9–10% v/v , in which it grows with great difficulty [ 27 , 28 , 29 ]. The Lt L3.1 strain showed an intermediate performance among the pool of strains at high and low temperature.…”
Section: Resultssupporting
confidence: 93%
“…It was statistically observed that the yeast with the lowest fermentation power was the F108 strain fermenting in the presence of low SO 2 and at low temperature (7.74 ± 0.04% v / v ), and the one that showed the highest fermentation power was the CONCERTO yeast (10.69 ± 1.32% v / v ) with low SO 2 and at high temperature. These results agree with previously reported information where the fermentative performance of the commercial strain Lt CONCERTO is really weak in a range of 9–10% v/v , in which it grows with great difficulty [ 27 , 28 , 29 ]. The Lt L3.1 strain showed an intermediate performance among the pool of strains at high and low temperature.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, it appears that the effect of temperature was not significant ( p >0.05) only in the case of fermentation with M02, as a similar amount of glycerol was produced at both temperatures. Similar concentrations of glycerol (4.4–5.2 g L −1 ), produced by S. cerevisiae , have been reported in an alcoholic beverage from dragon fruit [ 5 ], however, this yeast is capable of producing even higher amounts in the case of mead fermentation (>9.5 g L −1 ) [ 6 ].…”
Section: Resultsmentioning
confidence: 54%
“…Since PAB is a fermentation product, its main organoleptic characteristics are affected to a large extent by fermentation and especially by the microorganisms used, as was also proved in several fermented beverages made from red dragon fruit [ 5 ], diluted honey [ 6 ], Pilsner wort [ 7 ], apple juice [ 8 ] and grape juice [ 9 ]. Several studies reported that fermentation of pomegranate juice resulted in a completely new product with altered bioactive components, mainly due to reactions of polymerization, condensation, oxidation, hydrolysis, enzyme activity, and interactions of antioxidants with yeast cell walls [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…and ABTS .+ radical The scavenging capacity of the radicals observed from the DPPH and ABTS assays, as well as the presence of phenolic compounds in the fermented beverages can be attributed to the presence of the phenolic compound tyrosol (Souza et al, 2020). The content of phenolic compounds found in the fermented beverages was higher when compared to the fermented beverage with dragon fruit of 28.0 mg GAE L -1 elaborated by Souza and contributors (2018), and lower when compared to the fermented beverage from dragon fruit (H. costaricensis) of 280.6 mg GAE L -1 (Jiang et al, 2020). Resulted are expressed as means ± standard deviation (n=3).…”
Section: Antioxidant Capacity and Quantification Of Total Phenolsmentioning
confidence: 86%
“…The compounds glycerol, citric acid, and succinic acid were also found in the fermented beverage from dragon fruit (H. costaricensis). Higher glycerol content was observed in the fermentation with Saccharomyces cerevisiae when compared to different yeasts (Jiang et al, 2020). Glycerol is produced as a by-product of S. cerevisiae ethanolic fermentation process and is responsible for the smoothness and viscosity of wine (Scanes et al, 1998).…”
Section: H Nmr Analysis Of Juices and Fermented Beveragesmentioning
confidence: 96%